Investigating design, implementation and evaluation process of the model eliciting activities: the perspective of model eliciting principles - Sener, Zehra Taspinar; Dede, Yuksel (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
This study aims to reveal how model eliciting principles are used in the process of designing, applying, and evaluating teacher candidates' model-eliciting activities. This study was conducted in three stages in a multi-tiered teaching experiment. Firstly, 15 teacher candidates designed activities for Grade 7 students after they were trained on mathematical modeling. In the second stage, these activities were performed with Grade 7 students and video recorded. In the third stage, teacher candidates watched the videos and evaluated how model-eliciting principles were executed during instruction and revise their activities. To collect data, we used focus group interviews with teacher candidates, field notes, and reports. The findings revealed the two principles of reality and model construction to be at the fore during the design stage. The teacher candidates who watched the application videos found some problems in the principles of 'reality' 'self-assessment' and 'model generalization'. Teacher candidates following the applications, for the new design, offered recommendations for 'reality' and 'model construction' principles although the other principles were somewhat neglected. They did express that by making the proper arrangements to the learning environment, students would be able to acquire the other principles over time.
Keywords: Mathematical modeling; mathematics teacher candidates; Grade 7 students; model-eliciting activities; model-eliciting principles; EDUCATION; STUDENTS; Education & Educational Research